2017
DOI: 10.1088/2040-8986/aa74d5
|View full text |Cite
|
Sign up to set email alerts
|

Trap split with Laguerre-Gaussian beams

Abstract: The optical trapping techniques have been extensively used in physics, biophysics, micro-chemistry, and micromechanics to allow trapping and manipulation of materials ranging from particles, cells, biological substances, and polymers to DNA and RNA molecules. In this Letter, we present a convenient and effective way to generate a novel phenomenon of trapping, named trap split, in a conventional four-level double- atomic system driven by four femtosecond Laguerre-Gaussian laser pulses. We find that trap split … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…|1 is coupled to the excited levels |3 and |4 by control and probe fields E 31 and E 41 with carrier frequencies ω 31 and ω 41 , respectively. Two coupling fields E 32 (x, y) and E 42 (x, y) with carrier frequencies ω 32 and ω 42 couple the excited states to another lower state |2 . The spontaneous decay rates on the dipole-allowed transitions are denoted by γ 13 , γ 23 , γ 14 , and γ 24 .…”
mentioning
confidence: 99%
“…|1 is coupled to the excited levels |3 and |4 by control and probe fields E 31 and E 41 with carrier frequencies ω 31 and ω 41 , respectively. Two coupling fields E 32 (x, y) and E 42 (x, y) with carrier frequencies ω 32 and ω 42 couple the excited states to another lower state |2 . The spontaneous decay rates on the dipole-allowed transitions are denoted by γ 13 , γ 23 , γ 14 , and γ 24 .…”
mentioning
confidence: 99%
“…Moreover, the phase singularity of the LG modes on the beam axis dictates zero intensity at the beam center 46 , leading the intensity pattern of the LG modes to take the form of a doughnut or even concentric rings. It has been demonstrated that the characteristics of the optical phenomena can be influenced by the LG beams 47 – 49 . Mahmoudi et al showed that the use of LG beams narrowed the linewidth of the optical spectrum of the multi-photon resonance phenomena 50 .…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that the linewidth of the optical spectrum due to the multi-photon transition becomes narrower in the presence of a LG beam 15 . They have also studied trap split in an atomic system interacting with femtosecond LG laser pulses 16 . More recently, we have demonstrated that the LG beam can decrease the full width at the half maximum of the output probe intensity in the electromagnetically induced focusing 17 .…”
Section: Introductionmentioning
confidence: 99%